Розширення мережі мобільного зв’зяку на території запорізької ТЕС - Пушкарьов, В. В. (ХНУРЕ, 2020)
Today, there is a great need for extended mobile coverage in as many people's living or working areas as possible. This need is especially evident in industrial areas and large enterprises. The problem of low quality of mobile communication at such sites is connected with the complexity of the works on the design and placement of equipment in the industrial buildings of enterprises, the complexity of signal propagation through a large number of complex industrial metal structures in reinforced concrete structures. The purpose and task of the project is to develop project documentation for the construction of mobile base stations in the territory of TPP